Design and Prototyping of Weigh-In- Motion and Overload Protection System for Freight Vehicle - Pangestu Budi Utomo, Tegar
The high number of freight vehicles that experience overloading in Indonesia has led to a significant reduction in the age of road pavement. The overload detection system using weigh bridges has weaknesses in terms of time effectiveness. The use of Weigh-In-Motion (WIM) technology is a solution to these problems. The WIM device in this study used a bending plate sensor with one strain gauge. Tests are carried out using a motorcycle with one passenger under normal conditions and three passengers in overload conditions. The data obtained is stored using a data acquisition system for further analysis to obtain relations between the results of dynamic measurements and static mass of vehicles. Tests are carried out at speeds of 10, 20 and 30 km / h to study phenomena that appear at different speeds. At the end of the study, the system was developed using an Arduino microcontroller so that signal analysis can be done automatically. When the system detects an overload, it automatically alarms and the camera will be active. In this undergraduate assignment, a sensor system and signal analysis method for WIM devices have been developed. The average error obtained is in a sufficient range so that it is able to distinguish between overloaded and not vehicles. The development of systems with Arduino microcontrollers has also been successfully operated automatically and is able to provide keluaran in the form of alarms and cameras. Further development can still be done by adding a strain gauge and improving the device mounting method so that measurement errors are reduced. Other devices such as speed sensors, vehicle detection, communication systems, etc. need to be further investigated to make a complete WIM system.